Vibration-Based Finite Element Model Analysis on Dynamic Characteristics of Ultra-High Performance Concrete Beam - Jamadin, Adiza; Abdul Kudus, Sakhiah; Haziq Ya’akob, Ahmad Danial; Misnan, Mohamad Farid; Mohd Jaini, Zainorizuan (International Journal of Integrated Engineering, 2023)
Dynamic load analysis of Ultra-High-Performance Concrete (UHPC) beams is crucial, given the material's widespread use in bridges, enabling engineering feats like 100 meter single-span bridges. Structural vibration monitoring aids in evaluating a structure's ability to withstand dynamic loads, employing finite element (FE) model analysis for verification and enhancement. This study utilizes ANSYS for finite element modelling (FEM) and modal analysis, assessing the UHPC beam's structural integrity. An undamaged UHPC beam model validates dynamic properties, reducing disparities between analytical and experimental results. Modal properties of the first cracked and damaged UHPC beam are updated to represent actual conditions. Vibration analysis reveals inherent vibration modes, frequencies, and forms. Structural stiffness analysis verifies the relationship between stiffness and dynamic qualities. Experimental data updates the UHPC beam model, establishing a connection between structural stiffness and natural frequency under various conditions. In conclusion, ANSYS was employed for FEM, modal analysis, and parameterization verification, revealing the importance of accurate UHPC feature identification and meshing size. Discrepancies highlight the need for experimental tests, reducing differences between FEM and empirical findings. The numerical analysis in ANSYS underscores the correlation between structural stiffness and natural frequency, enabling precise structural health monitoring for UHPC beam damage or deterioration identification.